1994
DOI: 10.1159/000267482
|View full text |Cite
|
Sign up to set email alerts
|

Snellen Visual Acuity versus Pattern Reversal Visual-Evoked Response Acuity in Clinical Applications

Abstract: We compared the best-corrected Snellen acuity (SA) and the pattern reversal visual-evoked response (PVER) acuity in normal subjects and patients. Forty-two eyes of 42 normal subjects were controls; 457 eyes of 329 patients comprised the patient group. A steady-state stimulus with five check sizes ranging from 160 to 10 min in 1.0-octave steps was used. The PVER acuity was derived from the best-fit linear function relating the amplitude to the log-adjusted check size. Three intercepts of 0, 1 and 2 μV were used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
36
0

Year Published

1995
1995
2011
2011

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(36 citation statements)
references
References 17 publications
0
36
0
Order By: Relevance
“…In the previous studies [11,19,20,21,22], the SPVEP acuities calculated from both regression methods were greater than the logMAR visual acuity. In our study, we found that SPVEP acuity could be overestimated when a good visual acuity was involved, but underestimated when the visual acuity was poor.…”
Section: Discussionmentioning
confidence: 79%
“…In the previous studies [11,19,20,21,22], the SPVEP acuities calculated from both regression methods were greater than the logMAR visual acuity. In our study, we found that SPVEP acuity could be overestimated when a good visual acuity was involved, but underestimated when the visual acuity was poor.…”
Section: Discussionmentioning
confidence: 79%
“…4), flattening of the amplitude-check size function, and shift ing of the peak of the amplitude-check size function toward the larger checks, even with relatively good visual acuities. Ohn et al [21] reported that the PVER acuity does not al ways correlate with Snellen visual acuity, the former being poorer than the latter in patients with optic nerve disorders. Bull's eye maculopathies are another pathology that causes a disparity between the PVER and Snellen acui ties, which probably results from the unique anatomical damage.…”
Section: Discussionmentioning
confidence: 97%
“…The disappearance and/or prolongation of the main component of pVEP, named P100, is utilized to determine visual acuity objectively. There are several reports that Snellen and pVEP acuity show good correlation [15,16,26].…”
mentioning
confidence: 98%
“…Visual acuity examination is performed in many clinical situations in human medicine. The most common indicator of visual acuity in human beings is the Snellen fraction, which relates the ability of a subject to discriminate between letters or objects at a fixed distance [26,28]. This examination in humans requires the subject's response to judge the limit of visual recognition.…”
mentioning
confidence: 99%
See 1 more Smart Citation